Analisis Asuhan Keperawatan Pada Pasien dengan Diabetic Foot Ulcer dan Observasi Penerapan Madu Pada Perawatan Luka Kaki Diabetes di Ruang Perawatan Irina A Bawah RSUP. Prof. Dr. R. D. Kandou Manado - Didide, Christa; Masi, Gresty Natalia Maria; Pondaag, Ferlan Ansye (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2024)
Background: Wounds are not treated with proper nutrition, they will take a long time to heal and require pharmacological and non-pharmacological interventions. One non-pharmacological option that can be used is honey, because it contains antibiotics which function as antiseptic and antibacterial, providing protection to wounds and helping treat infections. Its anti-inflammatory properties contribute to pain relief, support circulation, and encourage the regeneration of new tissue, which can help eliminate tissue scarring on the skin (Tasalim, 2021). The aim of this scientific work is to explain nursing care for diabetic foot ulcer patients by treating wounds using honey. This case study method uses a descriptive method, with a nursing care process approach. The case study subjects were type 2 diabetes mellitus sufferers with diabetic foot wounds that had been around for more than 2 weeks. The subject of the case study was 1 person and was obtained randomly. The results of the case study before wound treatment with tilapia honey Bates-Jensen Wound Assessment Tool patient was 47 and after wound treatment with honey it was 41. Conclusions based on case studies of problems with skin/tissue integrity disorders with wound care interventions implemented for 5 days show that the results of using honey dressings to treat foot wounds in diabetics can reduce swelling in the area around the wound and minimize bleeding but there are no visible changes in granulation and epithelialization. Keywords: Honey, Diabetic Foot Ulcer